Luminescent properties of Y₃(Al;Ga)₅O₁₂: Tb thin films - Yousif, Abdelrhman Mohmmed Ahmed (University of the Free State, 2015)
The main aim of this project was to use the technique of pulsed laser depo- sition (PLD) to fabricate thin lms from Yttrium Aluminium Gallium Oxide (Y3(Al; Ga)5O12) doped with Tb3+ ions and then to investigate the structure, the morphology and the optical properties of the fabricated lms. Initially, the structure, morphology, luminescent properties and surface state be- fore and after 27 h of prolonged electron beam exposure of Y3(Al; Ga)5O12:Tb phosphor powder were determined, in order to understand the material and nd the necessary background that could assist in future research on this material. The electron irradiation was carried out at a base pressure of 2:3 10􀀀8 Torr and an oxygen pressure of 1:0 10􀀀6 Torr. New surface layers were formed after the chemisorbed species were removed as a result of electron stimulated surface chemical reactions. The rate of the removal of the chemisorbed species from the phosphors surface during prolonged electron irradiation was a ected by the background working atmosphere as measured with Auger electron spectroscopy combined with cathodoluminescence (CL) spectroscopy. The CL intensity of the Y3(Al; Ga)5O12:Tb stabilized after removal of the chemisorbed species and stayed constant during further electron irradiation, indicating that this phosphor is appropriate for the eld emission display technology. There was an increase in the Al, Y, O and Tb Auger peak intensities pointing to the formation of a complicated surface structure that was probably a combination of more than one chemical compound. X-ray photoelectron spectroscopy (XPS) results suggested electron-beam induced formation of new interleave oxide layers, such as AlOx, YOx and Y(Al; Ga)5O3 on the surface. These oxide layers acted as protective layers inhibiting further CL intensity degradation during the prolonged elec- tron irradiation. Moreover, the photoluminescence (PL) excitation and emission spectra of Tb3+ in the Y3(Al; Ga)5O12 phosphor were measured and analysed. The excitation spectrum was measured at an emission wavelength of 544 nm and the emission spectrum was measured at an excitation wavelength of 267 nm. The emission showed the well-known 5D4 !7 FJ(J = 6; 5; 4; 3) transitions of the Tb3+ ion. The main PL emission peak was due to the 5D4 !7 F5 tran- sition of Tb3+ with minor peaks at 489 nm (5D4 !7 F6), 590 nm (5D4 !7 F4) and 625 nm 5D4 !7 F3. Thin lms of the Y3(Al; Ga)5O12:Tb powder were grown on Si(100) substrates by the PLD technique using a Nd:YAG pulsed laser with a wavelength of 266 nm. The in uence of the working atmosphere (base pressure, O2, Ar and N2) on the morphology, structure and luminescence properties were investigated. The brightest emission was observed from the lm which was deposited in the O2 at- mosphere, indicating that oxygen was the best working atmosphere for growing the Y3(Al; Ga)5O12:Tb thin lms. The as deposited Y3(Al; Ga)5O12:Tb lms were amorphous in most cases and crystallized upon heat treatment. Heat treatments were applied to the lms for di erent annealing times and temperatures. Interesting phenomena occurred during the heat treatment which are summarized below: Firstly, the lms were annealed at 800 C, 1000 C and 1200 C for 3 hrs. The in uence of the annealing on the optical properties (excitation and the emission bands) and the crystal structure of the thin lm were monitored. X- ray di raction (XRD) and the XPS depth pro les indicated that there were annealing-induced changes in the crystal structure and chemical composition and consequent changes in the excitation bands. These changes (structure and composition) were attributed to interdi usion of atomic species between the substrate and the Y3(Al; Ga)5O12:Tb thin lm. The XRD and XPS data con- rm that after annealing, Y3(Al; Ga)5O12:Tb was converted to Y2Si2O7:Tb. A change in the relative ratios of the excitation band intensities was measured. Atomic force microscopy (AFM) showed that topographical changes also oc- curred during the annealing process. Thermoluminescence (TL) glow curves of the Y3(Al; Ga)5O12:Tb thin lms before and after annealing, indicated the pres- ence of di erent types of traps resulting from the change on the structure of the thin lms. Secondly, to avoid the changes on lm's structure and the optical properties, the lms were deposited on SiO2/Si(100) substrates rst and then annealed in air at 800 C, 900 C and 1000 C. AFM, XRD, PL, X-ray photoelectron spec- troscopy and Nano scanning Auger electron microprobe (NanoSAM) techniques have been applied to characterize these lms. The results were compared to previously investigated Y3(Al; Ga)5O12:Tb thin lms on Si(100) without an ox- ide (SiO2) layer. No change in the PL excitation bands as the result of post annealing was observed. Enhancement of the PL intensities was observed as a function of annealing temperatures, which was attributed to the improvement of the crystallization of the annealed lms. Annealing, however, caused stress in the lms and aggravated cracking occurred. Di usion of atomic species from the substrate to the lm's materials occurred, leading to phase changes and changes in stoichiometry. After annealing at higher temperatures, some regions on the lm's surface were enriched with Si were observed. Thirdly, to avoid severe chemical reactions between the Si substrate and the lm at higher annealing temperatures, the annealing time was shortened from 3 hrs to 1 h. The e ect of annealing the lms in air at 400 C and 800 C for 1 h was investigated. The three dimensional AFM images of the as-deposited lm shows well de ned spherically grains that were uniformly distributed over the surface with a root mean square (RMS) roughness value of 9 nm. After annealing at 800 C the surface became smooth and the RMS value was reduced to 6 nm. The smooth layer was con rmed to be a surface oxide layer enriched with Ga from the images captured using the NanoSAM. The PL intensities were observed to increase as a function of annealing temperature and this was attributed to the improvement of the crystallinity of the lms and a possible variation of the Ga concentration in the thin lms. In addition, CL properties of the lms were recorded when the lms were irradiated with a beam of electrons in the vacuum chamber of the Auger electron spectrometer. The CL intensity of the deposited lm was recorded as a function of electron dose as well as the accelerating volt- age. The CL has decreased to about 50% after 450 C/cm2 electron dose whilst increased with an increase in the accelerating voltage from 1 to 3 keV. Fourthly, the annealing e ect were studied further on the lms annealed at 800 C for 1 and 2 hrs in air. AFM showed an increase in grain size with an increase in annealing time. The PL emission spectrum presented similar characteristics for all di erent annealing times, and the emissions are explained by the well- known 5D4 !7 FJ(J = 6; 5; 4; 3) transitions of the Tb3+ ion. A new excitation band located at around 200 nm was observed from all the annealed lms which pointed to a change in the chemical environment, owing to the fact that, the 5d level depends strongly on the nature of the host due to a greater radial extension of the 5d orbital. Shift in the XRD peaks position to lower di rac- tion angles was also observed in the XRD results compared to the pattern of the Y3(Al; Ga)5O12:Tb powder and other thin lms. The new excitation band and the shift in the peak position of the XRD pattern were attributed to the enrichment of the annealed lms with Ga due to spreading phenomena of the agglomerated Ga particulates during the annealing process.
Thesis (Ph.D. (Physics))--University of the Free State, 2014
Keywords: Pulsed laser deposition; Thin films; Phosphors; Luminescence